2015
DOI: 10.1186/s12889-015-1798-y
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of peer support for improving glycaemic control in patients with type 2 diabetes: a meta-analysis of randomized controlled trials

Abstract: Background: To assess the effects of peer support at improving glycemic control in patients with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
109
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(121 citation statements)
references
References 46 publications
3
109
1
3
Order By: Relevance
“…A recent meta-analysis showed that peer support delivered through telephone calls were just as effective as in-person contacts for patients with diabetes. 23 This is particularly important because these authors also found that greater frequency of contact with peers was a critical factor for successful outcomes. Telephone-delivered support is a relatively low-cost, readily available means to facilitate contact frequency between patients and peer coaches.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis showed that peer support delivered through telephone calls were just as effective as in-person contacts for patients with diabetes. 23 This is particularly important because these authors also found that greater frequency of contact with peers was a critical factor for successful outcomes. Telephone-delivered support is a relatively low-cost, readily available means to facilitate contact frequency between patients and peer coaches.…”
Section: Discussionmentioning
confidence: 99%
“…Peer support can be defined as support from persons who have the same health condition as the people they assist and who experience similar challenges of those with the condition [10–12]. The use of lay mentors or community health care workers to support a lifestyle intervention, and reduce the very high costs of more intensive research interventions was recognized by the early triallists [3].…”
Section: Discussionmentioning
confidence: 99%
“…The costs of diabetes prevention intervention can be reduced by group based delivery [6] and the team who delivered the landmark study in this area recognised that ‘community health workers’ could be an attractive model for delivering lifestyle intervention at reduced cost [6]. There has been growing interest in this model over the last few years for the clinical management of Type 2 diabetes, and to a lesser degree in diabetes prevention [10–12]. Recent changes in the diagnostic criteria for diabetes, with a shift from glucose based criteria to one based on HbA1c, with a diagnostic threshold of an HbA1c ≥48 mmol/mol is widely supported and adopted [13, 14].…”
Section: Background and Rationalementioning
confidence: 99%
“…7 One recent meta-analysis looked at peer support for improv-ing glycemic control, yet this analysis included trials with community health workers and bilingual clinic employees as peer health coaches and was missing a few intervention trials that used people affected by diabetes as peer supporters. 8 Hence, to date, there has not been an adequate systematic review and meta-analysis of the overall effectiveness of peer support interventions delivered by people affected by diabetes to inform policy or potential health care delivery changes.…”
Section: Introductionmentioning
confidence: 99%